Natural variability in exposure to fine particles and their trace elements during typical workdays in an urban area. (August 2018) - Moreira, Camila A.B.; Squizzato, Rafaela; Beal, Alexandra; de Almeida, Daniela Sanches; Rudke, Anderson P.; Ribeiro, Marcos; Andrade, Maria de Fátima; Kumar, Prashant; Martins, Leila Droprinchinski
Graphical abstract: Highlights: Bus stations and traffic jam are the main spots of exposure to air pollution. PM2.5 exposure increases in periods with highest demands of buses. Sodium was associated to the presence of biodiesel in diesel. Workplaces close to traffic can cause health damage. In urban area the air inhaled by population contains Pb, Cr, Cu, Ni, Zn, Mn. Abstract: Studies on the natural human exposures to fine particulate matter (PM2.5 ) and their elements composition are practically non-existent in South America. In order to understand the natural exposure of the typical Brazilian population to PM2.5 and their trace element composition, we measured PM2.5 concentrations and collected mass on filters for nine continuous hours during a typical workday of volunteers. In addition, bus routes were performed at peak and non-peak periods, mimicking the routine activity of the population. Mean concentrations of PM2.5 in the bus and car groups were similar while the fraction of BCe was higher for the bus group. For all routes, mean PM2.5 concentrations were higher during peak than non-peak hours, with an average of 43.5 ± 33.1 μg m −3 and 14.3 ± 10.2 μg m −3, respectively. The trace elements S, K and Na originated mainly from vehicle emissions; Na was associated with the presence of biofuel in diesel. Toxic elements (Pb, Cr, Cu, Ni, Zn, Mn) were found at low levels as evident by the total hazard index that ranged from 2.15 × 10 −03 to 1.38 for volunteers. For all routes, the hazard index ranged from 2.25 × 10 −03 to 5.03. Average PM2.5 respiratory deposition dose was estimated to be 0.60 μg/kg-hour for peak hours. Potential health damages to people during their movements and at workplaces close to the traffic were identified. Improvements in the design of the building to reduce the entrance of air pollutants as well as the use of filters in the buses could help to limit population exposure.